Translating Takings: The Similarities of the Constitutional Protection of Property Rights in the United States and Germany - John N. Drobak (Washington University Global Studies Law Review, 2025)
Constitutional limitations on a government’s power to confiscate property, whether by an outright taking of title or by excessive regulation, are necessary both as a protection of an important personal right and as a foundation for economic growth. Both the Takings Clause of the United. States Constitution and Article 14 of the Basic Law of Germany serve this purpose. The scholars who have compared them have shown how unlike they are by focusing on the vast differences in the terms of the two provisions and the divergence in the analysis used by the Supreme Court and the German Constitutional Court in interpreting them. The German. Constitutional Court uses a more formal analysis and considers aspects of property ownership, such as personhood, which are not part of the Supreme Court’s takings jurisprudence. This article will show that despite these differences, both courts render remarkably similar decisions in similar cases. Notwithstanding its rhetoric, the Constitutional Court ends up usin a balancing test in its application of the “proportionality” principle, comparing the harm to the property owner against the benefit to society, while the Supreme Court does much the same. By focusing on outcomes, this article shows that the two clauses are effectively the same when applied by the two courts. This result is striking because Germany has a social democratic economy, while the United States has a free-enterprise market system In Part I, the article gives an overview of takings law, using Miller v. Schoene to illustrate aspects of the doctrine. In doing this, the article provides new insights into that classic case. Part II examines the constitutional protection of property rights in Germany and compares the factors that underlie takings analysis in Germany and the United States. This part concludes by showing the similarity of the decisions of both courts in comparable cases. Part III explains the reasons for the similarity in outcomes in both courts, focusing on the harmony in liberal tradition, social concerns, and economic performance. Part IV argues that the lessons of the article have a universal application to countries with a market economy.
Keywords: government’s power to confiscate property; government power; Constitutional limitations; Takings Clause; Article 14 of the Basic Law of Germany; German Constitutional Court; property ownership; personhood; proportionality principle